1988
DOI: 10.1136/bmj.296.6630.1156
|View full text |Cite
|
Sign up to set email alerts
|

Preceding infection as an important risk factor for ischaemic brain infarction in young and middle aged patients

Abstract: The role of preceding infection as a risk factor for ischaemic stroke was investigated in a case-control study of 54 consecutive patients under 50 years of age with brain infarction and 54 randomly selected controls from the community matched for sex and age. Information about previous illnesses, smoking, consumption of alcohol, and use of drugs was taken. A blood sample was analysed for standard biochemical variables and serum cholesterol, high density lipoprotein cholesterol, triglyceride, and fasting blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
134
1
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(148 citation statements)
references
References 37 publications
8
134
1
5
Order By: Relevance
“…Consistent with previous reports of increased stroke risk following infection, [31][32][33][34][35] our study demonstrates that patients with severe sepsis had a six-fold increased risk for in-hospital stroke compared with hospitalized patients without severe sepsis. Importantly, patients with severe sepsis who developed new-onset AF had a greater risk of in-hospital stroke than patients with pre-existing AF and individuals without a history of AF.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous reports of increased stroke risk following infection, [31][32][33][34][35] our study demonstrates that patients with severe sepsis had a six-fold increased risk for in-hospital stroke compared with hospitalized patients without severe sepsis. Importantly, patients with severe sepsis who developed new-onset AF had a greater risk of in-hospital stroke than patients with pre-existing AF and individuals without a history of AF.…”
Section: Discussionsupporting
confidence: 81%
“…Можно предпо-ложить, что в более возрастной группе не всегда можно воспроизвести четкую взаимосвязь между ФГ и смерт-ностью, о чем пишут немногочисленные авторы. Дей-ствительно Kannel WB., et al и Syrjanen J., et al пока-зали, что корреляция между уровнем ФГ и развитием осложнений от ССЗ особенно четко прослеживается у пациентов молодого и среднего возраста [35,36]. Кроме того, помимо возраста, можно предположить, что в нашем исследовании препараты, принимаемые (аспирин, статины и др.)…”
Section: Discussionunclassified
“…Previous studies have reported that acute infections, accompanied by acute-phase inflammation reactions and a prothrombotic state, are associated with an increased risk of acute vascular events, such as myocardial infarction and IS (Syrjänen et al, 1988;Lindsberg and Grau, 2003;Zeller et al, 2005). Susceptibility to infection/inflammation and/or risk of atherosclerosis and IS events were shown to be associated with genetic variations in genes and cytokine receptor genes (Worrall et al, 2003;Markus et al, 2006;Steinbrugger et al, 2009).…”
Section: Discussionmentioning
confidence: 99%